Nuclear Localization Signals for Optimization of Genetically Encoded Tools in Neurons - Karasev, Maksim M.; Baloban, Mikhail; Verkhusha, Vladislav V.; Shcherbakova, Daria M. (Frontiers in Cell and Developmental Biology, 2022)
Nuclear transport in neurons differs from that in non-neuronal cells. Here we developed a non-opsin optogenetic tool (OT) for the nuclear export of a protein of interest induced by near-infrared (NIR) light. In darkness, nuclear import reverses the OT action. We used this tool for comparative analysis of nuclear transport dynamics mediated by nuclear localization sequences (NLSs) with different importin specificities. We found that widely used KPNA2-binding NLSs, such as Myc and SV40, are suboptimal in neurons. We identified uncommon NLSs mediating fast nuclear import and demonstrated that the performance of the OT for nuclear export can be adjusted by varying NLSs. Using these NLSs, we optimized the NIR OT for light-controlled gene expression for lower background and higher contrast in neurons. The selected NLSs binding importins abundant in neurons could improve performance of genetically encoded tools in these cells, including OTs and gene-editing tools.